LINGUOCULTURAL ASPECT OF TEACHING RUSSIAN LANGUAGE IN THE CONDITIONS OF FORMATION OF BILINGUALISM - Ibragimova, Sayyora (Журнал иностранных языков и лингвистики, 2021)
The present article describes the methods that enhance students` vocabulary range who learn Russian language in « Russian language» module/Additionally, methods assist learners to employ vocabulary in learning process and create environment for communication in Russian language, and gain the skills such as analyzing the communicative situations, understanding the plot of various texts efficiently, also formulating the discursive situations in order to use Russian language.